Rapid-Testing Technology and Systems Improvement for the Elimination of Congenital Syphilis in Haiti: Overcoming the "Technology to Systems Gap". (22nd December 2013) - Severe, Linda; Benoit, Daphne; Zhou, Xi K.; Pape, Jean W.; Peeling, Rosanna W.; Fitzgerald, Daniel W.; Mate, Kedar S.
Abstract : Background . Despite the availability of rapid diagnostic tests and inexpensive treatment for pregnant women, maternal-child syphilis transmission remains a leading cause of perinatal morbidity and mortality in developing countries. In Haiti, more than 3000 babies are born with congenital syphilis annually. Methods and Findings . From 2007 to 2011, we used a sequential time series, multi-intervention study design in fourteen clinics throughout Haiti to improve syphilis testing and treatment in pregnancy. The two primary interventions were the introduction of a rapid point-of-care syphilis test and systems strengthening based on quality improvement (QI) methods. Syphilis testing increased from 91.5% prediagnostic test to 95.9% after (P < 0.001 ) and further increased to 96.8% (P < 0.001 ) after the QI intervention. Despite high rates of testing across all time periods, syphilis treatment lagged behind and only increased from 70.3% to 74.7% after the introduction of rapid tests (P = 0.27 ), but it improved significantly from 70.2% to 84.3% (P < 0.001 ) after the systems strengthening QI intervention. Conclusion . Both point-of-care diagnostic testing and health systems-based quality improvement interventions can improve the delivery of specific evidence-based healthcare interventions to prevent congenital syphilis at scale in Haiti. Improved treatment rates for syphilis were seen only after the use of systems-based quality improvement approaches.